Impact of heavy metal passivators on the nitrogenase activity and diazotrophic community in a cadmium-contaminated paddy field. (November 2022) - Jiang, Yuexi; Hu, Ting; Peng, Ou; Chen, Anwei; Tie, Baiqing; Shao, Jihai
Abstract: Passivators are frequently applied to deactivate heavy metal ions in soils and reduce availability of heavy metals to rice plant. However, few studies focus on response of function and diversity of the diazotrophic microorganisms toward heavy metal passivators. In this study, three kinds of heavy metal passivators, namely lime, silica fertilizer and gypsum, were applied to cadmium (Cd) contaminated paddy field. The effects of heavy metal passivators on diversity, abundance, expression of nifH gene, and nitrogen-fixation ability of soil diazotrophic bacteria were determined. The results showed that Proteobacteria was the main diazotrophic bacteria in paddy soils. The structure of diazotrophic community was not obviously affected by silica fertilizer or gypsum application but shifted by lime, with the characteristics of increasing the portions of δ- and γ- Proteobacteria but lowering those of α- and β- Proteobacteria relative to the Control. Rather than a decrease of bio-available Cd caused by passivator application, the variations of soil pH, bio-available silica, and soluble calcium significantly affected nitrogen-fixation ability, abundance and community structure of the diazotrophic bacteria in paddy soil. The results presented in this study are helpful to evaluate ecological effects of these heavy metal passivators on soil diazotrophic bacteria and are useful in management of biological nitrogen-fixation when those passivators was applied to remediate heavy metal contaminated paddy soils. Highlights: Lime application increased the nitrogen-fixation rate of diazotrophic bacterial. NifH gene expression was up-regulated after silica fertilizer application. Lime application induced the shifting of diazotrophic community. Variations of pH, available silicon and water-soluble calcium affected the community structure of diazotrophic bacterial.